Polish minischools. Microhistories of democracy and portraits of parental involvement - Mendel, Maria (International Journal about Parents in Education, 2023)
In light of cognitive and social advantages of thinking upon forms and meanings of the relationship between a subject and a place of its acting, and in light of my personal inexhaustible interest in the pedagogy of place (Mendel, 2006), I found it tempting to make an attempt of describing the existence (ontology) of a school in a specific place by using phenomenological and hermeneutical analyses. My aim was to academically describe how a school happens in a specific place, being a community event, or a social drama (Turner, 1974). I have made such an attempt and in this text I make an effort to present such a description by referring to a school situated in a Polish village; a school raison d’être of which is nowadays endangered; a school which is “too small” and the existence of which is refused in view of the poverty of Polish communes. As a researcher I decided that my research material will be various phenomena, that is various aspects of the school’s life embraced in available narrations. On the one hand, by describing, I tell the story of the school but, simultaneously, I analyze the story material (contents of narration). This is how my microhistory is created (Domańska, 2005). On the other hand, I reconstruct the unique picture of minischools created through the exchange of meanings which happens within the space of this story. It is a story about schools which firstly are doomed to be closed down as they are unprofitable and later are saved by social forces through being created a new within a new legal framework (by an association). Consequently, because of the fact that main characters of this story proved to be parents who – as all people of the post-communist Poland – look with hope at their sense of agency and a democratic aspect of the order in which they live, the text can be perceived as a microhistory of democracy.